2016
DOI: 10.3961/jpmph.16.073
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antiretroviral Therapy on the Survival of Human Immunodeficiency Virus-positive Adult Patients in Andhra Pradesh, India: A Retrospective Cohort Study, 2007-2013

Abstract: ObjectivesThe survival outcomes of antiretroviral treatment (ART) programs have not been systematically evaluated at the state level in India. This retrospective study assessed the survival rates and factors associated with survival among adult human immunodeficiency virus (HIV)-infected patients in Andhra Pradesh, India.MethodsThe present study used data from 139 679 HIV patients aged ≥15 years on ART who were registered from 2007 to 2011 and were followed up through December 2013. The primary end point was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 17 publications
5
17
0
Order By: Relevance
“…Further, the overall excess risk of death was 84% (HR = 1.84, 95% CI = 1.66-2.04) for 2007-08 period (CD4 ≤ 200 cells/mm 3 ), and 61% (HR = 1.61, 95% CI = 1.46-1.79) for 2009-11 period (CD4 ≤ 250 cells/mm 3 ) compared to 2012 onwards (CD4 ≤ 350 cells/mm 3 ) criteria. These findings are in agreement with other studies published from resource-limited settings [9,27,28]. An increased level of CD4 count is always linked with a decreased risk of a new AIDS event or death [29][30][31].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Further, the overall excess risk of death was 84% (HR = 1.84, 95% CI = 1.66-2.04) for 2007-08 period (CD4 ≤ 200 cells/mm 3 ), and 61% (HR = 1.61, 95% CI = 1.46-1.79) for 2009-11 period (CD4 ≤ 250 cells/mm 3 ) compared to 2012 onwards (CD4 ≤ 350 cells/mm 3 ) criteria. These findings are in agreement with other studies published from resource-limited settings [9,27,28]. An increased level of CD4 count is always linked with a decreased risk of a new AIDS event or death [29][30][31].…”
Section: Discussionsupporting
confidence: 92%
“…This indicates majority of these patients were accessed ART at the later stage of their disease, and explained by the fact that more than one-third (38.4%) of these patients had both CD4 cell count ≤ 200 cells/mm 3 and WHO clinical stage III/IV at the time of treatment start. Other Indian [9,16,18,19] and international [10,[33][34][35][36] studies conducted in the other low-and middle-income countries confirmed similar findings. Several self-perceived personal (such as service delivery, financial, personal health perception, and logistical) and structural barriers may also play a significant role in delaying ART accessing at the earlier stage [37].…”
Section: Viewpoints Paperssupporting
confidence: 68%
See 2 more Smart Citations
“…Patients with advanced stages or complicated cases were referred to MSH for terminal care, as it is an HIV-specialist hospital. A 7-year retrospective cohort study from India also reported a high mortality rate for such patients (Bajpai et al, 2016).…”
Section: Discussionmentioning
confidence: 96%